2005
DOI: 10.1007/s00018-005-5027-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of β-elemene in chemoresistant ovarian carcinoma cells is mediated through arrest of the cell cycle at the G2-M phase

Abstract: Elemene is a natural antitumor plant drug. However, the effect of elemene on cell growth in ovarian cancer is unknown. In this study, we show that beta-elemene inhibited the proliferation of cisplatin-resistant human ovarian cancer cells and their parental cells, but had only a marginal effect in human ovary cells, indicating differential inhibitory effects on cell growth between ovarian cancer cells and normal ovary cells. We also demonstrated for the first time that beta-elemene markedly enhanced cisplatin-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
105
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 51 publications
6
105
0
2
Order By: Relevance
“…We also showed that the antitumor effect of ß-elemene in non-small-cell lung cancer cells is mediated through induction of cell cycle arrest and apoptotic cell death (18). Furthermore, we demonstrated for the first time that ß-elemene markedly enhanced cisplatin-induced cytotoxicity in chemoresistant ovarian carcinoma cells (19). The effect and mechanism of ß-elemene in combination with other chemotherapeutic agents for malignancies are not elucidated, however, investigations have revealed differences in cell toxicity in vitro and side effects in vivo between ß-elemene and taxanes that suggest they may be suitable for use in combination.…”
mentioning
confidence: 63%
“…We also showed that the antitumor effect of ß-elemene in non-small-cell lung cancer cells is mediated through induction of cell cycle arrest and apoptotic cell death (18). Furthermore, we demonstrated for the first time that ß-elemene markedly enhanced cisplatin-induced cytotoxicity in chemoresistant ovarian carcinoma cells (19). The effect and mechanism of ß-elemene in combination with other chemotherapeutic agents for malignancies are not elucidated, however, investigations have revealed differences in cell toxicity in vitro and side effects in vivo between ß-elemene and taxanes that suggest they may be suitable for use in combination.…”
mentioning
confidence: 63%
“…The antitumor effect of β-elemene has been shown in some types of tumor, but the mechanism remains unclear. It has been reported that beta-elemene arrests chemoresistant ovarian carcinoma at the G2-M phase and inhibits the proliferation of cells (Li et al, 2005). Other reported that β-elemene could induce apoptosis in prostate cancer cells and lung tumor cells (Li et al, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…β-elemene is the active component (molecular formula C15H24, molecular weight 204.34), which has strong anti-tumor effects in vitro and in vivo (Wang et al, 2005;Yu et al, 2011;Li et al, 2011). The antitumor capability of β-elemene has been shown to display various types of cancers, such as glioma, breast carcinoma, liver cancer, leukemia, laryngeal cancer and ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
“…As the major active antitumor component, ß-elemene has been isolated as a monomeric drug and found to strongly induce apoptosis and antiproliferation in tumors or cells in vitro and in vivo (6)(7)(8)(9). The antitumor effect of ß-elemene has been demonstrated in the treatment of various tumors, such as glioma, liver cancer, breast carcinoma, leukemia, laryngeal cancer and ovarian cancer (7,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%